Group 3 dialkyl complexes of a rigid monoanionic NNN-donor pincer ligand: synthesis, structures, unexpected reactivity with CPh3+, and hydroamination catalysis. Issue 17 (5th April 2023) - Vasanthakumar, Aathith; Gray, Novan A. G.; Franko, Christopher J.; Murphy, Maia C.; Emslie, David J. H.
Abstract : A rigid new monoanionic pincer ligand was used to prepare yttrium and scandium dialkyl complexes, and reactivity with CPh3 + is described. Abstract : Palladium-catalyzed coupling of 4, 5-dibromo-2, 7, 9, 9-tetramethylacridan with two equivalents of 1, 3-diisopropylimidazolin-2-imine afforded 4, 5-bis(1, 3-diisopropylimidazolin-2-imino)-2, 7, 9, 9-tetramethylacridan, H[AII2 ]. Reaction of the H[AII2 ] pro-ligand with one equivalent of [M(CH2 SiMe3 )3 (THF)2 ] (M = Y or Sc) yielded the base-free neutral dialkyl complexes [(AII2 )M(CH2 SiMe3 )2 ] M = Y (1 ) and Sc (2 ). The rigid AII2 pincer ligand affords a similar steric profile to the previously reported XA2 pincer ligand, but is monoanionic rather than dianionic. Reaction of 1 with one equiv. of [CPh3 ][B(C6 F5 )4 ] in C6 D5 Br generated a highly active catalyst for intramolecular alkene hydroamination. However, rather than forming the expected monoalkyl cation, this reaction afforded a diamagnetic product which was identified as [(AII2 -CH2 SiMe3 )Y(CH2 SiMe3 )2 ][B(C6 F5 )4 ] (3 ; AII2 -CH2 SiMe3 is a neutral tridentate ligand with a central amine donor flanked by imidazolin-2-imine groups) in approx. 20% yield, accompanied by HCPh3 (∼2 equiv. relative to 3 ), an unidentified paramagnetic product (detected by EPR spectroscopy), and a small amount of colourless precipitate. The unexpected reactivity of 1 with CPh3 + is thought to involve initial AII2 ligand backbone oxidation, given that the zwitterionic form of the ligand contains a phenylene ring with two adjacent anionic nitrogen donors, similar to a redox-non-innocent, dianionic ortho -phenylenediamido ligand.